Distance, Symmetry, and Topology in Carbon Nanomaterials - Ashrafi, Ali Reza.; Diudea, Mircea V.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This contributed volume is inspired by the seminal discovery and identification of C60. Starting with a comprehensive discussion featuring graphene based nanostructures, subsequent chapters include topological descriptions of matrices, polynomials and indices, and an extended analysis of the symmetry and topology of nanostructures. Carbon allotropes such as diamond and its connection to higher-dimensional spaces is explored along with important mathematical and topological considerations. Further topics covered include spontaneous symmetry breaking in graphene, polyhedral carbon structures, nanotube junction energetics, and cyclic polyines as relatives of nanotubes and fullerenes. This book is aimed at researchers active in the study of carbon materials science and technology.
1. Molecular Dynamics Simulation of Carbon Nanostructures: The Nanotubes (István László) -- 2. Omega Polynomial in Nanostructures (Mircea V. Diudea) -- 3. An Algebraic Modification of Wiener and Hyper-Wiener Indices and their Calculations for Fullerenes (Fatemeh Koorepazan) -- 4. Distance under Symmetry: (3,6)-Fullerenes (Ali Reza Ashrafi) -- 5. Topological Symmetry of Multi-shell Clusters (Mircea V. Diudea) 6. Further Results on Two Families of Nanostructures (Zahra Yarahmadi) -- 7. Augmented Eccentric Connectivity Index of Grid Graphs (T. Došlić) -- 8. Cluj Polynomial in Nanostructures (Mircea V. Diudea) -- 9. Graphene Derivatives: Carbon Nanocones and Corsu Lattice - A Topological Approach (Farzaneh Gholaminezhad) -- 10. Hosoya Index of Splices, Bridges and Necklaces (Tomislav Došlic) -- 11. The Spectral Moments of a Fullerene Graph and their Applications (G. H. Fath-Tabar) -- 12. Geometrical and Topological Dimensions of the Diamond (G. V. Zhizhin) -- 13. Mathematical Aspects of Omega Polynomial (Modjtaba Ghorbani) -- 14. Edge-Wiener Indices of Composite Graphs (Mahdieh Azari) -- 15. Study of the Bipartite Edge Frustration of Graphs (Z. Yarahmadi) -- 16. The Hosoya Index and the Merrifield−Simmons Index of some Nanostructures (Asma Hamzeh) -- 17. Topological Indices of 3Generalized Fullerenes (Z. Mehranian) -- 18. Study of the Matching Interdiction Problem in some Molecular Graphs of Dendrimers (G. H. Shirdel) -- 19. Nullity of Graphs (Modjtaba Ghorbani) -- 20. Bondonic Chemistry: Spontaneous Symmetry Breaking of the Topo-Reactivity on Graphene (Mihai V. Putz) -- 21. Counting Distance- and Szeged (on Distances) Polynomials in Dodecahedron Nano-Assemblies (Sorana D. Bolboacă) -- 22. Tetrahedral Nanoclusters (Csaba L. Nagy) -- 23. Cyclic Carbon Polyynes (Lorentz Jäntschi) -- 24. Tiling Fullerene Surfaces (Ali Asghar Rezaei) -- 25. Enhancing Gauge Symmetries Via the Symplectic Embedding Approach (Salman Abarghouei Nejad) -- 26. A Lower Bound for Graph Energy of Fullerenes (Morteza Faghani).
Keywords: Nanotechnology; Chemistry, Physical and theoretical; Mathematical physics; Nanotechnology; Theoretical Chemistry; Mathematical Physics